2001
DOI: 10.1034/j.1600-0897.2001.d01-7.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital Mycoplasmosis in Rats: A Model for Intrauterine Infection1

Abstract: Mycoplasma pulmonis is an ideal model to study maternal genital infection during pregnancy, the impact of infections on pregnancy outcome, fetal infection, and maternal-fetal immune interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 26 publications
4
27
0
1
Order By: Relevance
“…Mycoplasma pulmonis UAB strain × 1048 was originally obtained from Maureen K. Davidson, University of Florida. Genital disease in SD rats with this mycoplasma strain is well characterized 5–9 . In order to ensure identical inocula for all experiments, a large‐volume culture was grown to late log phase in Frey's medium, aliquoted and frozen at −80°C.…”
Section: Mycoplasmasmentioning
confidence: 99%
See 4 more Smart Citations
“…Mycoplasma pulmonis UAB strain × 1048 was originally obtained from Maureen K. Davidson, University of Florida. Genital disease in SD rats with this mycoplasma strain is well characterized 5–9 . In order to ensure identical inocula for all experiments, a large‐volume culture was grown to late log phase in Frey's medium, aliquoted and frozen at −80°C.…”
Section: Mycoplasmasmentioning
confidence: 99%
“…Previous studies have demonstrated that intravenous inoculation at day 14 of gestation is the most efficient time point for inducing fetal infection 9 . Female rats at day 14 of gestation were anesthetized with a ketamine (Ketaset, Bristol Laboratories, Syracuse, NY, USA) xylazine (Rompun, Haver‐Lockhart, Shawnee, KS, USA) cocktail (100 mg ketamine + 150 mg xylazine) administered intraperitoneally at a dosage of 0.1 mL/100 g of body weight.…”
Section: Processing and Experimental Infection Of Ratsmentioning
confidence: 99%
See 3 more Smart Citations